Transforming Education through Artificial Intelligence Innovation: A Community Engagement for Advancing Technological Literacy - Prananda, Gingga; Judijanto, Loso; Stavinibelia, Stavinibelia; Ubaidillah, Ubaidillah; Ahyani, Edi; Yantiningsih, Erna (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
The development of Artificial Intelligence (AI) technology has had a significant impact across various sectors, including education. However, the understanding and application of AI in Indonesia's educational environment still face several challenges, such as low digital literacy and limited technological infrastructure. This community service activity aimed to enhance educators’ and education stakeholders’ literacy and understanding of the potential and challenges of using AI in the learning process. The activity was conducted in the form of a webinar titled “Educational Transformation Through Artificial Intelligence Innovation”, attended by 100 participants from diverse backgrounds. The materials presented covered fundamental AI concepts, its application in education, as well as relevant ethical and policy issues. Evaluation results showed an average increase of 60% in participants’ understanding scores after attending the webinar. In addition, over 95% of participants expressed satisfaction with the content delivered and showed interest in follow-up activities. This activity demonstrates that an educational approach through webinars is effective in improving AI literacy among educators and can serve as an initial step toward a more adaptive and inclusive educational transformation.